The Diversion Program Implementation Under the Juvenile Justice System Act in Indonesia: What Works, What Does Not? - Juwita Agustin Br Tobing, Septy (Restorative : Journal of Indonesian Probation and Parole System, 2024)
The Juvenile Justice System Act of Indonesia No 11 year 2012 that has been implemented in 2013 has brought some changes in how the criminal justice institutions in Indonesia managed the juvenile cases, including the correctional system. One of the most prominent things exhibited in this Act is the diversion program for juvenile offender as it would help to minimize the number of juvenile imprisonment and prevent them away from the juvenile court process. However, for the first five years of the implementation of this Act, there had no evaluation on how this diversion program had been carried out. This study aims to portray the effectiveness of the diversion programs based on the perceptions of 101 probation and parole officers in Indonesia who are involved in this study. The study result will help the practitioners and also the related stakeholders to improve the implementation of the diversion program. [Undang-undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak yang telah diimplementasikan pada tahun 2013 telah membawa sejumlah perubahan terkait bagaimana lembaga penegakan hukum di Indonesia menangani tindak pidana di bawah umur, termasuk sistem pemasyarakatan. Salah satu kebijakan yang paling menonjol yang diatur dalam undang-undang ini adalah program diversi bagi pelaku remaja, yang dapat membantu mengurangi jumlah pemenjaraan anak di bawah umur dan mencegah mereka menjalani proses sidang pengadilan remaja. Namun, selama lima tahun pertama implementasi kebijakan ini tidak pernah ada evaluasi mengenai pelaksanaan program diversi. Penelitian ini bertujuan untuk memaparkan efektivitas program diversi berdasarkan persepsi 101 orang Pembimbing Kemasyarakatan di Indonesia yang dilibatkan dalam penelitian ini. Hasil penelitian ini akan membantu para praktisi dan pemangku kepentingan (stakeholder) lain untuk memperbaiki implementasi program diversi.]